Times to Detection of Bacteria and Yeasts in BACTEC 9240 Blood Culture Bottles - Reisner, Barbara S. (American Society for Microbiology, 1999)
A 7-day incubation protocol was instituted with the BACTEC 9240 system for a 1-year period to determine the times to detection of clinically relevant organisms. A total of 23,686 blood and 693 sterile body fluid cultures were received; some cultures were held longer by special request. Of 1,609 likely skin contaminants, 42 were recovered on day 5, 34 on day 6, 16 on day 7, and 5 on day 8. Of 2,803 usual pathogens, 34 were recovered on day 5, 24 on day 6, 15 on day 7 and 1 on day 8. Twenty-one of the latter organisms were considered significant laboratory isolates because they were the first isolates from the respective patients. Chart review showed that 10 of 21 were considered clinically significant, but only 3 (all yeasts) affected the treatment of the patient. Our data show that 4 days of incubation were sufficient to recover all clinically relevant bacteria and 6 days were required to recover all clinically relevant yeasts.